Rising above vulnerability: resilience and sustainable livelihood outcomes of national park-adjacent communities in an African biodiversity hotspot - Kiconco, Michelle; Alinda, Kassim; Mbabazi, Immaculate Mary; Mutabazi, James; Ngunoue, Cynthia Kauami (Emerald, 2025)
Purpose – This study aims at investigating the ways in which resilience to livelihood stressors (shocks, displacement risk and seasonality) could influence sustainable livelihoods outcomes (improved well-being) of national park-adjacent communities in Uganda. Design/methodology/approach – With a sample of 364 respondents, data were obtained using a questionnaire survey and analyzed using structural equation modeling – with the aim of establishing the influence of resilience of national park-adjacent communities on their livelihood outcomes. Findings – The results show that resilient to shocks and seasonality are the most crucial factors in enhancing the livelihoods of national park-adjacent communities. Building community members’ resilience to shocks and seasonality has been shown to significantly improve the livelihoods of people residing near national parksinUganda. Originality/value – This paper expands the sustainable livelihood literature through an understanding of vulnerable national park-adjacent communities and stresses the influence of resilience to stressors on their livelihood outcomes. The research emphasizes the importance of enhancing community members’ livelihoods with a sharp focus on resilience to shocks and seasonality by integrating resilience strategies into tourism and livelihood policies.